Certain types of functions via $\boldsymbol{βθ}$-open sets - Caldas, Miguel (Sarajevo Journal of Mathematics, 2017)
New classes of functions, called somewhat $βθ$-continuous, somewhat $βθ$-open and hardly $βθ$-open functions, has been defined and studied by making use of $βθ$-open sets. Characterizations and properties of these functions are presented.